2018
DOI: 10.1021/acsami.8b07573
|View full text |Cite
|
Sign up to set email alerts
|

Membraneless Compartmentalization Facilitates Enzymatic Cascade Reactions and Reduces Substrate Inhibition

Abstract: Living cells possess membraneless organelles formed by liquid-liquid phase separation. With the aim of better understanding the general functions of membraneless microcompartments, this paper constructs acellular multicompartment reaction systems using an aqueous multiphase system. Membraneless coacervate droplets are placed within a molecularly crowded environment, where a larger dextran (DEX) droplet is submerged in a polyethylene glycol (PEG) solution. The coacervate droplets are capable of sequestering rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 70 publications
(101 reference statements)
2
80
0
Order By: Relevance
“…The different local environments experienced by biomolecules (e.g.,i nt erms of viscosity, dielectric constant, pH, …) can affect their activity.I na ddition, the differential sequestration of enzymes,s ubstrates, intermediates and products within the droplets can result in decreasedr eactivity (e.g.,i ft he droplets sequester an enzyme but exclude its substrate). [81] Overall, these studies indicate that the extentso fp artitioning of biomolecules into one or the other phase produced by LLPS can strongly affect the rates of biochemical reactions. [80] The phenomenon known as substrate inhibition has also been reported as ap lausible cause of reduced enzyme reactivity:i n one study dextranase was shown to be inactivated when sequestered in dextran-rich droplets, due to the high local concentration of substrate dextranm acromolecules.…”
Section: Bridging the Gap With Living Cells:i Ntracellular Biomoleculmentioning
confidence: 82%
See 2 more Smart Citations
“…The different local environments experienced by biomolecules (e.g.,i nt erms of viscosity, dielectric constant, pH, …) can affect their activity.I na ddition, the differential sequestration of enzymes,s ubstrates, intermediates and products within the droplets can result in decreasedr eactivity (e.g.,i ft he droplets sequester an enzyme but exclude its substrate). [81] Overall, these studies indicate that the extentso fp artitioning of biomolecules into one or the other phase produced by LLPS can strongly affect the rates of biochemical reactions. [80] The phenomenon known as substrate inhibition has also been reported as ap lausible cause of reduced enzyme reactivity:i n one study dextranase was shown to be inactivated when sequestered in dextran-rich droplets, due to the high local concentration of substrate dextranm acromolecules.…”
Section: Bridging the Gap With Living Cells:i Ntracellular Biomoleculmentioning
confidence: 82%
“…Osmotic pressure differences across semipermeable membranes have been exploited to induce changes in the local concentrations of encapsulated phase-separating species and therefore to induce phase separation. Dextranase, for instance, has been used to hydrolyse dextran into smaller oligosaccharides and hence to trigger the dissolution of dextran-rich droplets suspended in aP EG-rich phase [81] or embedded within ah ydrogel, [123] resulting in the gradualr eleaseo fs equestered proteins. [78b] Similarly,m ultistep osmotic shocks applied to lipid vesicles containing cell lysate and PEG were shown to induce lysate phase separation due to liposome shrinkage, resulting in localised protein expression.…”
Section: Biochemical Alteration Of Concentrations Of Llps-prone Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Conveniently, this type of LLPS and stable molecule partitioning phenomena can be produced outside the cell using readily available aqueous solutions made from common polymers such as poly(ethylene glycol) (PEG) and dextran (DEX) in place of IDPs and nucleic acids (Figure A). Since our first applications in highly‐parallel gene delivery and knockdown (Figure ), we have expanded the microfluidic use of aqueous two phase systems (ATPS) to stem cell patterning, construction of physically segregated but chemically communicating bacteria communities, cross‐reaction free immunoassays, and preparation of membrane‐less organelle mimetic reaction systems …”
Section: Embracing and Utilizing Disordermentioning
confidence: 99%
“…Since our first applications in highlyparallel gene delivery and knockdown [13] (Figure 5), we have expanded the microfluidic use of aqueous two phase systems (ATPS) to stem cell patterning, [14] construction of physically segregated but chemically communicating bacteria communities, [15] cross-reaction free immunoassays, [16] and preparation of membrane-less organelle mimetic reaction systems. [17] Beyond the mainly technological use of the ATPSs that result from the LLPS of PEG and DEX solutions as is performed in my lab and as briefly described above, there have been significant advances in understanding of LLPS of protein and nucleic acid solutions in the cell beyond formation of nucleoli. There is even a category of disease referred to as intrinsically disordered protein diseases where abnormal intracellular LLPS formation may be a contributing factor.…”
Section: Embracing and Utilizing Disordermentioning
confidence: 99%